ANALISIS PENGELOLAAN KEUANGAN BADAN USAHA MILIK DESA (BUMDes) BERDIKARI DESA CITALI KECAMATAN PAMULIHAN - Nurwanda, Putri (PT Naureen Digital Education, 2025)
This study aims to analyze the financial management of BUMDes Berdikari in Citali Village, Pamulihan District. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The analysis refers to Government Regulation No. 11 of 2021 concerning BUMDes management, which includes aspects of planning, recording, accountability, and supervision. The results of the study show that financial planning is carried out when there is an increase in capital through the preparation of a Budget Plan (RAB) in meeting forums. Financial records have been maintained through the preparation of balance sheets and income statements. Accountability is reported to advisors and supervisors through deliberation meetings. Supervision is conducted through direct visits and monthly evaluation meetings. The financial management practices of BUMDes Berdikari have reflected principles of accountability and transparency, although improvements are still needed in terms of managerial capacity and documentation.